(untitled) (BIRDEM Medical Journal, 2019)
Background: A raised serum uric acid is recognized as an unfavourable fetal outcome of pre-eclampsia. The objective of this study was to determine the relationship between hyperuricemia and fetal outcome in preeclamptic patients. Methods: This observational study was carried out in the Department of Gynecology and Obstetrics of BIRDEM General Hospital from July 2015 to June 2016. Fifty pre eclamptic pregnant women with hyperuricemia (group A) and 50 preeclamptic pregnant women with normal serum uric acid level (group B) were taken as study subjects. Data were analyzed by SPSS where p value less than 0.05 was considered significant. Results: Mean age of the patients was 25.88 ± 4.52 years and 24.30 ± 5.09 years in group A and group B respectively. Mean serum uric acid level was 7.19±0.62 mg/dl in group A and 4.83±0.73 mg/dl in group B. Maximum (66%) patients were primigravida in group A and 34% in group B. In this study, intra-uterine death (IUD) occurred in 4 (8%) cases in group A and in 1 (2%) case in group B, intra-uterine growth retardation (IUGR) was 20 (40%) cases in group A and 4 (8%) cases in group B, low birth weight was in 38 (76%) cases in group A and 21(42%) cases in group B. Occurrence of IUGR and low birth weight was significantly higher in group A than group B. APGAR score was significantly lower in group A (5.10±1.61) than that of group B (6.36±1.32). Neonatal intensive care unit (NICU) referral was more in group A (60%) than group B (20%). Conclusion: It can be concluded that hyperuricemia is a predictor of poor fetal outcome in pre-eclamptic women. Birdem Med J 2019; 9(2): 117-120